How to Expand Repurchase Intention? The Intervening Impact of Attitude towards Mobile Shopping - Lutfi Nurcholis; Raditya Ferdianto (Bina Nusantara University, 2021)
The development of information technology has a significant impact on almost all activities in various fields,such as shopping. The perceived benefit and lower risk factors are significant factors for shopping on the Internet.However, the problem in shopping activities is the security risk factor in transactions and the lack of publicknowledge and trust. There is a research gap in the relationship between perceived benefits and risks with purchaseintention. Based on the phenomenon, the research aimed to investigate and test the attitude toward mobileshopping as a mediating variable at the relationship between perceived usefulness and perceived risk againstrepurchase intention. The research applied a quantitative approach to explain the relationship between researchvariables. The used sampling technique was purposive sampling with several criteria, with a total sample of 200mobile shopping users in Central Java. Data collection was carried out using a questionnaire. The obtained datawere processed using the SPSS 16. The results show that perceived usefulness and perceived risk affect attitudein mobile shopping and repurchase intention significantly. Then, attitude toward mobile shopping also influencerepurchase intention. Last, it also finds that attitude toward mobile shopping can mediate the relationship betweenperceived usefulness and perceived risk against repurchase intention.